Valve-Like and Protruding Calcified Intimal Flap Complicating Common Iliac Arteries Kissing Stenting - George S. Georgiadis; Efstratios I. Georgakarakos; Nikolaos Schoretsanitis; Christos C. Argyriou; George A. Antoniou; Miltos K. Lazarides (Case Reports in Vascular Medicine)
Endovascular therapy for iliac artery chronic total occlusions is nowadays associated with low rates of procedure-related complications and improved clinical outcomes, and it is predominantly used as first-line therapy prior to aortobifemoral bypass grafting. Herein, we describe the case of a patient presenting with an ischemic left foot digit ulcer and suffering complex aortoiliac lesions, who received common iliac arteries kissing stents, illustrating at final antegrade and retrograde angiograms the early recognition of a blood flow obstructing valve-like calcified intimal flap protruding through the stent struts, which was obstructing antegrade but not retrograde unilateral iliac arterial axis blood flow. The problem was resolved by reconstructing the aortic bifurcation at a more proximal level. Completion angiogram verified normal patency of aorta and iliac vessels. Additionally, a severe left femoral bifurcation stenosis was also corrected by endarterectomy-arterioplasty with a bovine patch. Postintervention ankle brachial pressure indices were significantly improved. At the 6-month and 2-year follow-up, normal peripheral pulses were still reported without intermittent claudication suggesting the durability of the procedure. Through stent-protruding calcified intimal flap, is a very rare, but existing source of antegrade blood flow obstruction after common iliac arteries kissing stents.